Berezinskii-Kosterlitz-Thouless phase transitions with long-range couplings - Giachetti, Guido; Defenu, Nicolò; Ruffo, Stefano; Trombettoni, Andrea (Physical review letters, 2021)
The Berezinskii-Kosterlitz-Thouless (BKT) transition is the paradigmatic example of a topological phase transition without symmetry breaking, where a quasiordered phase, characterized by a power-law scaling of the correlation functions at low temperature, is disrupted by the proliferation of topological excitations above the critical temperature TBKT. In this Letter, we consider the effect of long-range decaying couplings ∼r−2−σ on the BKT transition. After pointing out the relevance of this nontrivial problem, we discuss the phase diagram, which is far richer than the corresponding short-range one. It features—for 7/4<σ<2—a quasiordered phase in a finite temperature range Tc<T<TBKT, which occurs between a symmetry broken phase for T<Tc and a disordered phase for T>TBKT. The transition temperature Tc displays unique universal features quite different from those of the traditional, short-range XY model. Given the universal nature of our findings, they may be observed in current experimental realizations in 2D atomic, molecular, and optical quantum systems.